2018
DOI: 10.2174/1567205015666180411092551
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Treatment Enhances Aβ Lymphatic Clearance in a Transgenic Mouse Model of Amyloidosis

Abstract: The data expands on our prior report that the lymphatic system participates in Aβ clearance from the brain. We propose that abnormalities in Aβ clearance through the lymphatic system may contribute to the development of cerebral amyloidosis. Melatonin and related indole molecules (i.e., indole- 3-propionic acid) are known to inhibit Aβ aggregation although they do not reverse aggregated Aβ or amyloid fibrils. Therefore, these substances should be further explored in prevention trials for delaying the onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 0 publications
0
57
0
1
Order By: Relevance
“…> 1 µM, and at these concentrations metabolism is dominant. A recent study on appearance of Aβ in lymph nodes may also reflect the behaviour at higher concentrations as it was performed in mice with mutant APP and high Aβ production rate [ 425 ].…”
Section: Clearance Of Specific Substancesmentioning
confidence: 99%
“…> 1 µM, and at these concentrations metabolism is dominant. A recent study on appearance of Aβ in lymph nodes may also reflect the behaviour at higher concentrations as it was performed in mice with mutant APP and high Aβ production rate [ 425 ].…”
Section: Clearance Of Specific Substancesmentioning
confidence: 99%
“…An important recent observation by Pappolla and co-workers indicate that the administration of melatonin to AD transgenic mice augments the glymphatic clearance of Aβ (132). Relevant to this, melatonin is known to preserve slow wave sleep in patients (148).…”
Section: Resultsmentioning
confidence: 96%
“…As for the experiments of Table 1, theoretical human equivalent doses calculated from Table 3's results ranged from 2-to 3-orders of magnitude greater than those employed in humans. (132) The way in which melatonin exerts its inhibitory effect on the generation of Aβ remains undefined. Melatonin interacts with Aß40 and Aß42 and inhibits progressive β-sheet and/or amyloid fibrils (133,134), an interaction which appears to depend on structural melatonin characteristics rather than on its antioxidant properties (133).…”
Section: Evidence For the Therapeutic Value Of Melatonin In Animal Momentioning
confidence: 99%
“…Interestingly, melatonin's pleiotropic effects on the immune system contribute significantly to preventing amyloidogenesis in the brain . Recently, it has been reported that melatonin facilitates Aβ clearance from the brain into the peripheral lymphatic system in a transgenic mouse model (Tg2576), which is clearly evident by an increase in Aβ in the cervical and axillary lymph nodes . Such studies may further lead to investigate the underlying mechanisms of melatonin action on the lymphatic clearance, which would prevent the accumulation of both Aβ and tau.…”
Section: Melatonin Regulates Immune and Inflammatory Signaling In Neumentioning
confidence: 99%